Analisis Efisiensi Pemasaran Jagung (Zea mays) di Kabupaten Wonogiri - Dea Arien Alinda Dewi; Darsono Darsono; Agustono Agustono (Universitas Muhammadiyah Malang, 2018)
This study aims to determine the market structure, behavior and performance of maize marketing in Wonogiri District. The basic research method is analytical descriptive. The research location was chosen purposively. The farmers sample were determined by using quota sampling, while traders sample were chosen by using snowball sampling method. The research data is analyzed by SCP approach (Structure, Conduct, and Performance of Market). The research results showed that the market structure of maize in Wonogiri District leads to the incomplete market competition, namely oligopsony market. This market structure causes the inefficient market. The market conduct is inefficient, it is showed by the β1 (0.785) <1. There are four types of maize marketing channel in Wonogiri District with the farmer’s share more than 50%. It indicates that the maize marketing in Wonogiri District is included in efficient category.